Transcriptome-wide selection and validation of a solid set of reference genes for gene expression studies in the cephalopod mollusk Octopus vulgaris - Imperadore, Pamela; Cagnin, Stefano; Allegretti, Vittoria; Millino, Caterina; Raffini, Francesca; Fiorito, Graziano; Ponte, Giovanna (Frontiers in Molecular Neuroscience, 2023)
Octopus vulgaris is a cephalopod mollusk and an active marine predator that has been at the center of a number of studies focused on the understanding of the neural and biological plasticity. Studies on the machinery involved in e.g., learning and memory, regeneration, neuro-modulation are required to shed light on conserved and/or unique mechanisms that these animals evolved. Analysis of the gene expression is one of the most essential means to expand our understanding of the biological machinery, and the selection of an appropriate set of reference genes is the prerequisite for quantitative real-time polymerase chain reaction (qRT-PCR). Here we selected 77 candidate reference genes (RGs) from a pool of stable and relatively high expressed transcripts identified from the full-length transcriptome of O. vulgaris, and evaluated their expression stabilities in different tissue through geNorm, NormFinder, Bestkeeper and RefFinder. Although various algorithms provided different assemblage of the most stable reference genes for different kind of tissues here tested, comprehensive ranking revealed RGs specific to the nervous system (Ov-RNF7 and Ov-RIOK2), and Ov-EIF2A and Ov-CUL1 across all considered tissues. Furthermore, we validated RGs assessing the expression profiles of nine target genes (Ov-Naa15, Ov-Ltv1, Ov-CG9286, Ov-EIF3M, Ov-NOB1, Ov-CSDE1, Ov-Abi2, Ov-Homer2, Ov-Snx20) in different areas of octopus nervous system (gastric ganglion, as control). Our study allowed us to identify the most extensive set of stable reference genes currently available for the nervous system and appendages of adult O. vulgaris.